Descartes' cogito : saved from the great shipwreck - Sarkar, Husain (Cambridge University Press, 2003)
Perhaps the most famous proposition in the history of philosophy is Descartes' cogito 'I think therefore I am'. Husain Sarkar claims in this provocative new interpretation of Descartes that the ancient tradition of reading the cogito as an argument is mistaken. It should, he says, be read as an intuition.